The conserved apicomplexan Aurora kinase TgArk3 is involved in endodyogeny, duplication rate and parasite virulence. (22nd February 2016) - Berry, Laurence; Chen, Chun‐Ti; Reininger, Luc; Carvalho, Teresa G.; El Hajj, Hiba; Morlon‐Guyot, Juliette; Bordat, Yann; Lebrun, Maryse; Gubbels, Marc‐Jan; Doerig, Christian; Daher, Wassim
Summary: Aurora kinases are eukaryotic serine/threonine protein kinases that regulate key events associated with chromatin condensation, centrosome and spindle function and cytokinesis. Elucidating the roles of Aurora kinases in apicomplexan parasites is crucial to understand the cell cycle control during Plasmodium schizogony or Toxoplasma endodyogeny. Here, we report on the localization of two previously uncharacterized Toxoplasma Aurora‐related kinases (Ark2 and Ark3) in tachyzoites and of the uncharacterized Ark3 orthologue in Plasmodium falciparum erythrocytic stages. In Toxoplasma gondii, we show that TgArk2 and TgArk3 concentrate at specific sub‐cellular structures linked to parasite division: the mitotic spindle and intranuclear mitotic structures (TgArk2), and the outer core of the centrosome and the budding daughter cells cytoskeleton (TgArk3). By tagging the endogenous PfArk3 gene with the green fluorescent protein in live parasites, we show that PfArk3 protein expression peaks late in schizogony and localizes at the periphery of budding schizonts. Disruption of the TgArk2 gene reveals no essential function for tachyzoite propagation in vitro, which is surprising giving that the P. falciparum and P. berghei orthologues are essential for erythrocyte schizogony. In contrast, knock‐down of TgArk3 protein results in pronounced defects in parasite division and a major growth deficiency. TgArk3‐depleted parasites display several defects, such as reduced parasite growth rate, delayed egress and parasite duplication, defect in rosette formation, reduced parasite size and invasion efficiency and lack of virulence in mice. Our study provides new insights into cell cycle control in Toxoplasma and malaria parasites and highlights Aurora kinase 3 as potential drug target.